Materialising Migration: Towards a Theory of Integration in Isiac Cults - Mazurek, Lindsey A. (NTT, 2021)
This paper studies Italian migrants to Greece from the third to the first century BCE and their involvement in Egyptian cults. I focus on two case study sites: Delos and Thessaloniki. At both sites, Italians played a small but active role through introduction of new structures and objects that helped them integrate into local social and religious communities. These migrants, then, saw integration as an often-desirable process. But the evidence also indicates that Italians strove to preserve their membership in Italian communities as well as Greek ones, suggesting that integration here is episodic, situational, and does not erase existing cultural identity.